2019
DOI: 10.1177/0825859719827316
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Decisional Control Preferences of a Cohort of Patients With Advanced Cancer Receiving Palliative Care in India

Abstract: Context: Frequency of passive decisional control preferences (DCPs) has been variably reported but is generally higher among patients living in developing countries. Objectives: This prospective cross-sectional study aimed to determine the frequency of passive DCP among patients with advanced cancer in a tertiary cancer center in India and to identify its association with their sociodemographic and clinical characteristics. Methods: Patients with advanced cancer referred to palliative care (between March and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…In overall grading, among eight cross-sectional studies, four studies 22,23,26,31 were of good quality, three 25,28,33 were of moderate quality and one study 29 was found to have poor quality. As per the adapted grading system, the qualitative study 24 and non-randomized before-after intervention study 27 were graded as the good quality study as well.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In overall grading, among eight cross-sectional studies, four studies 22,23,26,31 were of good quality, three 25,28,33 were of moderate quality and one study 29 was found to have poor quality. As per the adapted grading system, the qualitative study 24 and non-randomized before-after intervention study 27 were graded as the good quality study as well.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…No studies were found from Afghanistan, Bhutan, or the Maldives. Most of the (n = 10) intervention took place at the hospital or clinic level [21][22][23][24][25][26][27][28][29][30] whereas some (n = 3) were based on community setting [31][32][33] .…”
Section: Systematic Review Processmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, PS assessment helps in identifying patients with palliative care needs (Maas et al, 2013; Lee et al, 2019), and it is frequently included in the criteria of referral to outpatient palliative care (Hui et al, 2016). Furthermore, the PS of patients may have an impact on their decision-making preferences (Ghoshal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%